SELF MANAGEMENT PROGRAM AMONG TYPE 2 DIABETES MELLITUS PATIENTS: A LITERATURE REVIEW - Rian Adi Pamungkas; Dodik Limansyah; Sudarman Sudarman; Brajakson Siokal (Belitung Nursing Journal, 2016)
Background: Diabetes mellitus is a crucial problem that leads to serious multiple complication. Self-management program is an essential foundation for the empowerment approach, and necessary for patients to effectively manage their behaviors. Purpose: The purpose of this study is to describe, compare and critique six existing self-management programs that are commonly used to guide self-management for type 2 Diabetes Mellitus (DM) patients. Method: An integrative review was conducted. Relevant studies published in English language and retrieved from CINAHL, PubMed, Science Direct, and Google search were included. Results: Five Randomized Control Trials (RCTs) and one quasi-experimental study were reviewed. Goal setting and action planning combined with other strategies (brief counseling, problem solving, and follow-up strategy) showed more effective to improve behavioral change and several clinical outcomes. Continuing follow-up through telephone-call and face to face follow-up becomes the essential element for successful behavior change. Conclusion: Diabetes self-management program is effective to improve behavioral change and clinical outcomes among patients with type 2 DM. Further research is needed to test the effectiveness of self-management combine with other strategies which are goal setting strategy and follow-up strategy in patients with type 2 DM.